1989
DOI: 10.1021/bi00448a016
|View full text |Cite
|
Sign up to set email alerts
|

Construction of an artificial bifunctional enzyme, .beta.-galactosidase/galactose dehydrogenase, exhibiting efficient galactose channeling

Abstract: The in-frame fusion between two oligomeric enzymes, beta-galactosidase and galactose dehydrogenase, is described. The lacZ gene was fused to the 3' end of the galdh gene with a linker encoding only three amino acids. The purified artificial bifunctional enzyme displayed the enzymic activity of both gene products. The hybrid protein was found in two major forms, consisting of four and six subunits, but other forms could also be identified. The molecular weight of each subunit was determined to be 145,000 by sod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
45
1
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(47 citation statements)
references
References 24 publications
0
45
1
1
Order By: Relevance
“…Another fusion protein of ␤-galactosidase and galactose dehydrogenase was also shown to exist as two major forms, consisting of four or six subunits, as well as other forms (21). Unlike these reports, due to the monomeric nature of the ␣1,3GalT, both fusion proteins f1 and f2 in the present study exist as homodimers.…”
Section: Discussioncontrasting
confidence: 48%
See 2 more Smart Citations
“…Another fusion protein of ␤-galactosidase and galactose dehydrogenase was also shown to exist as two major forms, consisting of four or six subunits, as well as other forms (21). Unlike these reports, due to the monomeric nature of the ␣1,3GalT, both fusion proteins f1 and f2 in the present study exist as homodimers.…”
Section: Discussioncontrasting
confidence: 48%
“…Significantly, the reaction rates in producing Gal␣1,3Lac from UDP-Glc and lactose are increased 4-and 1.5-fold by f1 and f2, respectively, in comparison with the native enzymes. This result can be explained by the substrate channeling effect (21), indicating that the UDP-Gal produced by the epimerase is captured faster by the transferase moiety in either f1 or f2 than that in the system of native enzymes. Furthermore, the higher activity of f1 over f2 suggests that the active sites for the epimerase and ␣1,3-galactosyltransferase part are in a more optimal configuration in f1.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…no intrinsic differences in the structures of each enzyme moiety in the fusion enzyme and the individual enzymes, even though TPSP was slightly more stable than the TPS/TPP mixture. Still, some studies showed that the fusion enzyme was more stable against thermal denaturation than the individual enzymes were (16,30).…”
Section: Discussionmentioning
confidence: 99%
“…Such proximity allows a reaction intermediate to be directly transferred to the active site of the next enzyme in a sequential enzyme complex. By preventing serious diffusion of the intermediate, the reaction rates of whole enzymatic processes could be increased (2,13,22). Recently, we reported that a bifunctional fusion enzyme resulting from fusion between T6P synthase and trehalose 6-phosphatase of E. coli exhibited increased catalytic activity during trehalose synthesis (20).…”
Section: Discussionmentioning
confidence: 99%